2005
DOI: 10.1002/mds.20474
|View full text |Cite
|
Sign up to set email alerts
|

Double‐blind, placebo‐controlled, unforced titration parallel trial of quetiapine for dopaminergic‐induced hallucinations in Parkinson's disease

Abstract: We completed a single site, double-blind, placebo-controlled, parallel design study of quetiapine for hallucinations in PD. Thirty-one subjects with PD and prominent visual hallucinations and Mini-Mental State Examination score >21 were randomly assigned in a 2:1 drug to placebo ratio, up to 200 mg daily of quetiapine or matching placebo given in two doses. They were seen at 3 weeks (100 mg/day) and 12 weeks (200 mg/day, with optional dose reduction). Evaluation included the Unified Parkinson's Disease Rating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
156
0
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 265 publications
(166 citation statements)
references
References 39 publications
2
156
0
5
Order By: Relevance
“…Quetiapine, another atypical antipsychotic drug, has been reported in a number of open-label studies to reduce psychosis in PD without worsening motor symptoms, but sedative and hypotensive effects also limit its tolerability (Fernandez et al, 1999Reddy et al, 2002;Mancini et al, 2004;Morgante et al, 2004;Merims et al, 2006). Furthermore, in three placebo-controlled, double-blind, randomized trials, quetiapine failed to show superiority to placebo on measures of psychosis in PDP (Ondo et al, 2005;Rabey et al, 2006;Shotbolt et al, 2009). Nevertheless, it remains widely used as the initial drug treatment for PDP, at doses from 25 to 300 mg/day, and is the drug of choice for PDP according to the American Academy of Neurology Practice Parameters Task Force on the treatment of PD (Miyasaki et al, 2006); clozapine is recommended only after quetiapine fails to manage psychotic symptoms (Chou et al, 2007;Reddy et al, 2002;Mancini et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Quetiapine, another atypical antipsychotic drug, has been reported in a number of open-label studies to reduce psychosis in PD without worsening motor symptoms, but sedative and hypotensive effects also limit its tolerability (Fernandez et al, 1999Reddy et al, 2002;Mancini et al, 2004;Morgante et al, 2004;Merims et al, 2006). Furthermore, in three placebo-controlled, double-blind, randomized trials, quetiapine failed to show superiority to placebo on measures of psychosis in PDP (Ondo et al, 2005;Rabey et al, 2006;Shotbolt et al, 2009). Nevertheless, it remains widely used as the initial drug treatment for PDP, at doses from 25 to 300 mg/day, and is the drug of choice for PDP according to the American Academy of Neurology Practice Parameters Task Force on the treatment of PD (Miyasaki et al, 2006); clozapine is recommended only after quetiapine fails to manage psychotic symptoms (Chou et al, 2007;Reddy et al, 2002;Mancini et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Quetiapine is not licensed for the treatment of PDP despite being listed as a therapeutic option in guidelines. [5][6][7][8]14 However, data from double-blind, randomized controlled trials evaluating quetiapine in patients with PDP have been mixed, 13 with four studies reporting no significant improvement in symptoms of psychosis over placebo, [15][16][17][18] and one study reporting a significant decrease in hallucinations. 19 A new atypical antipsychotic, pimavanserin, received regulatory approval in the US in April 2016 for the treatment of hallucinations and delusions associated with PDP.…”
mentioning
confidence: 99%
“…Open label studies showed quetiapine to be well tolerated and an effective antipsychotic for PDP [96][97][98] and in comparison trial [95] to be non-inferior to clozapine. Unfortunately, three double blind controlled trials did not find efficacy [99][100][101], although all confirmed that the drug was free of motor worsening. One small DBPCT study [102] did find efficacy and tolerance but the numbers are too small to be persuasive.…”
Section: Managementmentioning
confidence: 99%